NUTRIENT COMPOSITION, FERMENTATION QUALITY, in vitro DEGRADABILITY, AND METHANE EMISSIONS OF WHOLE-CROP CORN SILAGES TREATED WITH ARBUSCULAR MYCORRHIZAL FUNGI BIOFERTILIZERS DURING PLANTING - Ridla , Muhammad; Prihantoro, Iwan; Prastiwi Gamasari, Emiralda (Chilean Journal of Agricultural & Animal Sciences, 2025)
Silage fermentation quality and nutrient composition are significantly influenced by the raw material used before ensiling, including agronomic practices such as fertilizer application. This study evaluated the effects of different levels of Arbuscular Mycorrhizal Fungi (AMF) biofertilizer applied during corn cultivation on nutrient composition, silage fermentation characteristics, in vitro rumen fermentation dynamics, and methane emissions. Corn plants were harvested 82 days post-planting, cut 10 cm above ground level, and manually chopped into pieces of 3–5 cm in length. The chopped forage was packed into 10-liter silos, compacted to expel air, and sealed to ensure anaerobic conditions. All samples were ensiled for 30 days. A completely randomized design was employed with three AMF biofertilizer levels (0, 10, and 20 g per planting hole) and six replications. Data were analyzed using ANOVA followed by Tukey’s test for multiple comparisons. The results indicated that AMF application had a limited effect on nutrient composition but significantly increased (P < 0.05) water-soluble carbohydrate (WSC) content, which is crucial for efficient fermentation. All silages were well preserved, as evidenced by a pH below 4. Enhanced in vitro rumen fermentation, indicated by increased total short-chain fatty acid (TSCFA) production, higher gas output, and a slight improvement in degradability, was associated with higher WSC content. Elevated WSC levels also contributed to reduced methane emissions by promoting more efficient microbial fermentation.